The second coming of Paisley : militant fundamentalism and Ulster politics - Jordan, Richard L. (Richard Lawrence), 1956- (Irish studies., 2013)
This book examines the relationship between the Reverend Ian Paisley and leaders of the militant wing of evangelical fundamentalism in the United States. The author convincingly demonstrates that it was exposure to the ideas and principles of leaders of the Christian right such as Carl McIntire and Billy James Hargis that enabled Paisley to develop a militant brand of politicized religious fundamentalism that he used with remarkable success to block the advance of civil rights for Northern Ireland's Catholic population. -- From publisher's description.